IMPLEMENTASI PENGGUNAAN LIBAGI SNAKE AND LADDER LEARNING MEDIA DI SEKOLAH DASAR - Puspitasari, Indah; Khoirinnissa, Afifah; Okta Fiya, Hesti; Risky, Annisa; Kusuma P, Tiara (PGSD STKIP PGRI Pacitan, 2024)
The Snakes and Ladders game is a traditional game played by at least two people, using dice and a board with figures of snakes and ladders. It is the the development result of the Snakes and Ladders game which includes multiplication and division. The research aims to describe the implementation of Libagi snakes and ladders media in class 5 to improve numeracy skills through learning while playing. This research uses a descriptive qualitative method, the study aimed at describing the application of Libagi learning media in class 5 of SD Negeri 2 Sambong. The results can be concluded that 18 of 21 students were able to solve every problem in the pawn stop box.